2015
DOI: 10.1134/s1063773715080022
|View full text |Cite
|
Sign up to set email alerts
|

IGR J17463-2854, a possible symbiotic binary system in the galactic center region

Abstract: This paper is devoted to determining the nature of the hard X-ray source IGR J17463-2854 located toward the Galactic bulge. Using data from the INTEGRAL and Chandra X-ray observatories, we show that five point X-ray sources with approximately identical fluxes in the 2-10 keV energy band are detected in the error circle of the object under study. In addition, significant absorption at low energies has been detected in the spectra of all these sources. Based on data from the VVV (VISTA/ESO) infrared Galactic Bul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This, of course, requires a knowledge of an extinction law in the direction to the source. It is especially important, taking into account preliminary estimates of the distance to GRO J1750−27 as > 12 kpc (Scott et al 1997;Shaw et al 2009) and a number of previous publications, where it was shown that the extinction law for the central regions of the Galaxy might significantly differ from the standard one (see, e.g., Nishiyama et al 2009;Revnivtsev et al 2010;Karasev et al 2010Karasev et al , 2015Alonso-García et al 2017;Karasev & Lutovinov 2018). For the following analysis we used the absorption law and extinction ratios in different filters, obtained by Alonso-García et al (2017) from the VVV survey data for the Galactic Center direction.…”
Section: Ir Counterpart: Type and Distance Estimatementioning
confidence: 99%
“…This, of course, requires a knowledge of an extinction law in the direction to the source. It is especially important, taking into account preliminary estimates of the distance to GRO J1750−27 as > 12 kpc (Scott et al 1997;Shaw et al 2009) and a number of previous publications, where it was shown that the extinction law for the central regions of the Galaxy might significantly differ from the standard one (see, e.g., Nishiyama et al 2009;Revnivtsev et al 2010;Karasev et al 2010Karasev et al , 2015Alonso-García et al 2017;Karasev & Lutovinov 2018). For the following analysis we used the absorption law and extinction ratios in different filters, obtained by Alonso-García et al (2017) from the VVV survey data for the Galactic Center direction.…”
Section: Ir Counterpart: Type and Distance Estimatementioning
confidence: 99%
“…Our results are based on the use of narrow vertical strips to determine the colors of RCGs in different filters and the extinction law. This method was proposed by Karasev et al (2015) and developed further in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, note that bulge RCGs have been comprehensively studied previously, and the general approaches are well known (see, e.g., Paczynski and Stanek 1998;Dutra et al 2003;Revnivtsev et al 2010;Gontcharov and Bajkova 2013). This section is based on the method proposed by Karasev et al (2015) to determine the local extinction by in-vestigating the distribution of RCGs in narrow strips perpendicular to the Galactic plane. The strip width is 2 , which allows the scatter of distances to RCGs due to the variability of the bulge structure along the Galactic longitude to be minimized (Nishiyama et al 2009;Gonzalez et al 2012).…”
Section: Determining the Absolute Magnitudes Of Rcgs In The Z And Y F...mentioning
confidence: 99%
“…After the aforementioned compilation by [114], [115] reported the first detection of the X-ray emission from eight more symbiotic systems using Swif t/XRT, thus bringing the total number of known symbiotic systems as X-ray sources to 33 (see also [38]). 561213) [120], IGR J17164-3803 [121] and IGR J17463-2854 [122].…”
Section: Symbiotic Starsmentioning
confidence: 99%